The development of adsorbent based natural gas storage for vehicle application - Mat, Hanapi; Zakaria, Zainal; Mohd. Norddin, Mohd. Noorul Anam; Tan, Siu Ming; Terry, George Paou (Universiti Teknologi Malaysia, 2000)
Storage of natural gas by adsorption has a potential to replace Compressed Natural Gas (CNG) in mobile storage applications, such as in vehicles. Storage by adsorption at moderate pressure of 500 psig could be expected to reduce the problem of bulky high-pressure CNG storage within a confined space used in vehicle. In adsorptive storage, the amount of gas stored at lower pressure increases when a large portion of gas adsorbs on the adsorbent. However, its capacity and performance depend on adsorbent types and properties. This study is focused on the storage capacity and delivery performance of Adsorptive Natural Gas (ANG) storage employing different types of commercial adsorbents which were carried out by performing experimental work on an ANG storage system. Methane adsorptive storage was done in a 0.5-liter adsorbent-filled gas vessel under isothermal and dynamic conditions. The ANG vessel was charged with methane up to 500 psig at different rates of filling and was discharged under dynamic condition at a varied rate of discharge. The results show that the storage capacity obtained under isothermal condition is higher than under dynamic condition due to continuous temperature rise experienced during dynamic charging. Higher storage capacities were obtained for adsorbent with larger surface area and micropore volume but smaller interparticle void. Adsorbent that has high heat capacity and low heat of methane adsorption yields lesser temperature rise during adsorption and lesser temperature fall during desorption. Consequently, these characteristics lead to a better storage and delivery capacities. At faster charging rate, lower storage capacity was obtained and faster discharging rate caused inefficient gas delivery. Under cyclic operation, adsorbents performances deteriorate when adsorbent structure is gradually damaged under high-pressure operation. Among the adsorbents tested, palm shell activated carbon shows the highest storage and delivery capacity which are 87.4 V/V and 75.8 V/V respectively.